Resistance to Temptation as a Mediator in the relation between Types of Mood and Internet addiction among University students - Faries Haron Rashid; Ali Abdulraheem Salih (Zanco Journal of Humanity Sciences)
Abstract: This study aims to identify resistance to temptation as a Mediator in the relation between types of mood and internet addiction in university students. The sample for the study consisted of (300) students, they are chosen by using random style with equal distribution. In order to measure this aim, the research adopted scales for resistance to temptation, types of mood and internet addiction. The results of the study refers to there are have types of mood (fearfulness, distress and anger) and Internet addiction in university students, but there are not have that resistance to temptation. As well as that lack of resistance to temptation plays the role of the mediator variable in the relationship between types of mood and internet addiction in university students.